Formation of the Legal Framework for State and Municipal Services in the CIS Member States - S. L. Sergevnin; I. S. Alekhina; A. K. Soloveva (Евразийская интеграция: экономика, право, политика, 2024)
The research is aimed at studying the normative legal acts of the CIS member states regulating the provision of state and municipal services in the CIS member states.Aim. To identify approaches to the formation of terminological foundations of the legal institute of state and municipal services, to the definition of the range and legal position of the participants of legal relations, to the regulation of the order of provision (rendering) of state and municipal services.Tasks. To consider legislative approaches, terms used in the sphere of public/service services, the development of the topic in scientific literature. To analyze regulatory legal acts of the CIS member states in the sphere of state and municipal services.Methods. The research was conducted using comparative legal method.Results. The study has shown that legal regulation of provision of state and municipal services is carried out in all CIS member states, the terminological apparatus is mainly presented, while the diversity of definitions and approaches to the provision of service services, which is manifested not only in relation to state and municipal services, but also in connection with the provision of services in various life situations, as well as public services and services to the business environment, is noted. The results are presented in the form of generalized models of legal regulation of state and municipal services in the CIS.Conclusions. At present, in the legislation of the CIS member states, despite the different approaches to the formation of the terminological foundations of the legal institution of state and municipal services, the definition of the range and legal status of participants in the process of providing (rendering) state and municipal services, regulating the procedure for providing (rendering) state and municipal services, there are prerequisites for the harmonization of legal principles and norms in the area under study.